MDMA-Assisted Therapy as a Means to Alter Affective, Cognitive, Behavioral, and Neurological Systems Underlying Social Dysfunction in Social Anxiety Disorder - Luoma, Jason; Lear, M. Kati (Frontiers in Psychiatry, 2021)
Social anxiety disorder (SAD) is a prevalent and often debilitating psychiatric disorder that can assume a chronic course even when treated. Despite the identification of evidence-based pharmacological and behavioral treatments for SAD, much room for improved outcomes exists and 4-methylenedioxymethamphetamine (MDMA) has been proposed as a promising adjunctive treatment to psychological interventions for disorders characterized by social dysfunction. A small randomized, placebo-controlled trial of MDMA-assisted therapy (MDMA-AT) for social anxiety in autistic adults offered encouraging results, but more research is sorely needed to explore the potential for MDMA-AT in treating SAD. This review aims to stimulate future study by summarizing research on disruptions in neurological, perceptual, receptive, and expressive systems regulating social behavior in SAD and proposing how MDMA-AT may alter these systems across four domains. First, we review research highlighting the roles of social anhedonia and reduced social reward sensitivity in maintaining SAD, with specific attention to the reduction in positive affect in social situations, infrequent social approach behaviors, and related social skills deficits. We posit that MDMA-AT may enhance motivation to connect with others and alter perceptions of social reward for an extended period following administration, thereby potentiating extinction processes, and increasing the reinforcement value of social interactions. Second, we review evidence for the central role of heightened social evaluative threat perception in the development and maintenance of SAD and consider how MDMA-AT may enhance experiences of affiliation and safety when interacting with others. Third, we consider the influence of shame and the rigid application of shame regulation strategies as important intrapersonal processes maintaining SAD and propose the generation of self-transcendent emotions during MDMA sessions as a mechanism of shame reduction that may result in corrective emotional experiences and boost memory reconsolidation. Finally, we review research on the role of dysfunctional interpersonal behaviors in SAD that interfere with social functioning and, in particular, the development and maintenance of close and secure relationships. We discuss the hypothesized role of MDMA-AT in improving social skills to elicit positive interpersonal responses from others, creating a greater sense of belonging, acceptance, and social efficacy.